Techno-Economic Risk Analysis Study of Co2 and Hydrogen Utilization From Refinery as Raw Material for Production of Dimethyl Ether - Suriperdana, Puan Chairunnisa; Sommeng, Andy Noorsaman; Nengkoda, Ardian (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The existence of carbon footprint trade regulations and advances in carbon capture, utilization, and storage (CCUS) technology have led to the urgency of CCUS installations at all refineries globally. Captured CO2 can be used as a new economic opportunity by being reprocessed as a raw material for the production process. CO2 can be processed into DME through dry methane reforming, methanol synthesis, and methanol dehydration processes. The Indonesian government plans to replace LPG with DME. Thus, a process simulation using Aspen Plus was carried out to see the effectiveness of production along with an investment feasibility analysis in terms of NPV, IRR, PBP, and PI values and a probability review using Monte Carlo simulation. From the simulation on Aspen Plus, DME was produced as much as 868.04 tons/day. Furthermore, the economic parameters were calculated with a DME selling price of USD 1,300/ton and obtained an NPV value of USD 1,783,715,566.19, IRR 58.44%, PBP 2.041 years, and PI 3.675 so that the plant can be said to be feasible. From 1000 iterations carried out in the simulation, the four economic parameters show positive values so that the financial risk of the plant is relatively safe.